Why Moffet Matters Now - Stephen Lafer; Jonathan M. Marine (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
James Porter Moffett (1929–1996) was a ground-breaking teacher, author, and theorist of language learning who had a profound impact on the fields of English Education, Language Arts, Composition, and Educational Psychology in the mid to late 20th century and was the first member of the Assembly for Expanded Perspectives on Learning (AEPL). In the inaugural Moffett’s Corner, Steve Lafer and Jonathan Marine discuss how they came together, why they wanted to start this column, and what they hope to accomplish.
Keywords: James Moffett